Profil Senyawa Metabolit Sekunder dan Deteksi Antosianin pada Buah Stroberi (fragaria x ananassa) Menggunakan Kromatografi Lapis Tipis dan Spektrofotometri Inframerah: Profile of Secondary Metabolite Compounds and Anthocyanin Detection in Strawberry Fruit (Fragaria x ananassa) Using Thin-Layer Chromatography and Infrared Spectrophotometry - Haikal, Muhammad Wildan; Rahayu, Tintrim; Jayanti, Gatra Ervi (FMIPA UNISMA, 2025)
Strawberry plants are a type of plant that grows extensively in Indonesia. Some studies show that Strawberries (Fragaria x ananassa) are a source of bioactive compounds, rich in ascorbic acid, anthocyanins and phenol compounds, and have high levels of antioxidants. Strawberries have compounds that provide pigment and antioxidant activity, namely anthocyanins. This study aims to detect secondary metabolite compounds in strawberry fruit extract (Fragaria x ananassa) using Thin Layer Chromatography (TLC) with a mobile phase containing butanol, acetic acid, and aqua-distillate (4:1:1) and infrared spectrophotometry. The results of phytochemical screening tests showed that the strawberry extract contained secondary metabolite compounds, including alkaloids, flavonoids, tannins, and saponins. TLC with the Rf value in Strawberry fruit extract results in 0.38. The results of the infrared spectrophotometry analysis indicate the presence of functional groups, including C-H, CO, OH, C꓿C, and ꓿C-O-C, which corroborate the results of TLC, suggesting that the strawberry extract contains anthocyanins. Keywords: strawberry, secondary metabolite compound, TLC, infrared spectrophotometry ABSTRAK Tanaman stroberi merupakan tanaman yang banyak tumbuh di Indonesia. Tanaman stroberi memiliki banyak manfaat terutama bagian buahnya. Buah stroberi (Fragaria x ananassa) adalah sumber senyawa bioaktif, kaya akan asam askorbat, antosianin dan senyawa fenol, dan memiliki kadar antioksidan yang cukup tinggi. Buah stroberi memiliki senyawa yang memberi pigmen dan mempunyai aktivitas antioksidan yaitu antosianin. Penelitian ini bertujuan untuk mengetahui profil senyawa metabolit sekunder pada ekstrak buah stroberi dan mendeteksi senyawa antosianin pada ekstrak buah stroberi (Fragaria x ananassa) menggunakan Kromatografi Lapis Tipis (KLT) dengan fase gerak butanol-asam asetat-aquadest (4:1:1) dan FTIR. Hasil uji skrining fitokimia menunjukkan bahwa ekstrak stroberi mengandung senyawa metabolit sekunder alkaloid, flavonoid, tanin dan saponin. Hasil KLT ditunjukkan dengan nilai Rf pada ekstrak buah stroberi adalah 0,38. Hasil analisis spektrofotometri inframerah terdapat gugus fungsi O–H, C=O, C=C dan =C–O–C yang memperkuat hasil KLT bahwa ekstrak stroberi mengandung antosianin. Kata kunci: stroberi, antosianin, metabolit sekunder, KLT, FTIR